Persistence, Discontinuation, and Switching Patterns of Newly Initiated TNF Inhibitor Therapy in Ankylosing Spondylitis Patients in the United States - Theresa Hunter; Krista Schroeder; David Sandoval; Atul Deodhar (Rheumatology and Therapy, 2019)
Abstract Introduction The primary goals of treating ankylosing spondylitis (AS) patients are to maximize long-term health-related quality of life through control of symptoms and inflammation, prevention of progressive structural damage, and preservation of function. The objective of this study was to describe treatment patterns (persistence, discontinuations, and switch) in the 2 years following the initiation of tumor necrosis factor inhibitors (TNFi) therapy in AS patients. Methods Adult patients with ≥ 2 AS diagnostic codes (ICD-9: 720.0 and/or ICD-10:M45.x) by a healthcare provider were included in this retrospective analysis of data from the IBM MarketScan Commercial Claims database. Patients who newly initiated a TNFi from 01/01/2009 to 12/31/2013 were indexed on their first TNFi. Patients were required to have a 1-year pre-index period free of TNFi and continuous enrollment 1-year pre-index and 2-year post-index. Patients were excluded if they had ≥ 2 diagnostic codes for any of the following conditions: rheumatoid arthritis, juvenile idiopathic arthritis, psoriatic arthritis, Crohn’s disease, ulcerative colitis, plaque psoriasis, hidradenitis suppurativa, or uveitis. Demographic, clinical, and treatment patterns were analyzed. Treatment patterns included switching to a new TNFi, discontinuation (≥ 90-day gap in therapy without starting a new TNFi), or persistence (no gaps in therapy ≥ 90 days) during the 2-year follow-up period. Logistic regression analyses predicting persistent vs. non-persistent and switching vs. discontinuation were conducted. Results A total of 1372 AS patients (846 males/526 females) met the inclusion criteria for this study. Males had a mean age of 44.3 years, while females had a mean age of 42.3 years. Adalimumab was the first biologic for the majority of patients (44.6% males/43.3% females), followed by etanercept (40.4% males/41.6% females), infliximab (10.4% males/10.8% females), golimumab (4.6% males/3.8% females), and certolizumab pegol (0.0% males/0.4% females). During the follow-up period, 33.1% of patients (n = 454) were persistent on their index TNFi, 40.7% (n = 559) discontinued their index TNFi and did not restart a TNFi, and 26.1% (n = 359) switched to a second TNFi. Patients prescribed cDMARDs were more likely to be persistent, while females and opioid users were less likely to be persistent on their first TNFi. Among those that discontinued their first TNFi, 32.8% (n = 187) of males and 43.6% (n = 177) of females switched to a second TNFi. Conclusions This study suggests that approximately 67% of male AS patients and 77% of female AS patients newly initiating a TNFi do not remain on the index therapy 2 year post initiation. Funding Eli Lilly and Company.